Anticipatory postural adjustments as a function of response complexity in simple reaction time tasks. (25th September 2018) - Kennefick, Michael; Wright, Alexander D.; Smirl, Jonathan D.; van Donkelaar, Paul
Highlights: Reaction time was lengthened as the task became more complex. APA profiles were scaled to the complexity of the task. APAs are preplanned to maintain balance while successfully completing a complex task. Abstract: The central nervous system preplans postural responses to successfully perform complex multi-joint movements. These responses have been termed anticipatory postural adjustments (APAs), and they constitute a general type of response to stabilize posture prior to movement initiation. APA sequences are elicited with shorter latency when a startling acoustic stimulus is applied, demonstrating their preplanned nature. Increasing task complexity using a simple reaction time (RT) paradigm has been shown to delay limb movement RT as a result of additional planning or sequencing requirements; however, the effect of task complexity on APA dynamics is unclear. The purpose of the present study was to investigate if task complexity modulates APA onset in a manner analogous to that observed in the primary effector. 13 participants completed 150 trials of simple (1-target) and complex (2- or 3-target) arm movements while standing on a force plate. Results indicated participants had significantly faster arm movement RTs in the simple versus the most complex condition. Similar to the primary effector, APA RTs were longer in the most complex (3-target) movement compared to both the 1-target and 2-target movements. Furthermore, APA excursion velocities were scaled to the complexity of the upcoming movement: the rate of APAs increased from simplest to most complex movements. These findings clearly demonstrate APAs are sensitive to task complexity, further elucidating their preplanned role in stabilizing posture which enables the successful completion of intended movements.